Stochastic excitation of gravity waves in rapidly rotating massive stars. Issue Volume 9:Issue S307(2014) (23rd January 2015) - Mathis, S.; Neiner, C.
Abstract: Stochastic gravity waves have been recently detected and characterised in stars thanks to space asteroseismology and they may play an important role in the evolution of stellar angular momentum. In this context, the observational study of the CoRoT hot Be star HD 51452 suggests a potentially strong impact of rotation on stochastic excitation of gravito-inertial waves in rapidly rotating stars. In this work, we present our results on the action of the Coriolis acceleration on stochastic wave excitation by turbulent convection. We study the change of efficiency of this mechanism as a function of the waves' Rossby number and we demonstrate that the excitation presents two different regimes for super-inertial and sub-inertial frequencies. Consequences for rapidly rotating early-type stars and the transport of angular momentum in their interiors are discussed.